Intra-swarm migration of size-variable robotic modules utilizing the Brazil nut effect. (1st September 2020) - Joshi, Devwrat Omkar; Shimizu, Masahiro; Hosoda, Koh
Abstract : In this work, we apply physical granular segregation phenomena to the problem of intra-swarm module migration in a robotic swarm. These segregation phenomena allow for complex relative motion between interacting particles on the basis of differing physical properties. In particular, the Brazil nut effect is one such phenomenon that causes segregation of particles based on relative size difference. We simulated size-variable modules in order to take advantage of this effect and induce intra-swarm module migration. Intra-swarm module migration refers to the movement of the modules within the confines of the swarm, relative to each other, as well as the swarm container. We introduced two methods to produce different kinds of module movement. The first of these, called the flashlight method, induced movement of an individual module relative to its neighbours. The second, called the zone method, induced an orientation-aligned global module motion within the swarm. In this work, we evaluate the effects of different parameters on the nature of the movements induced by these methods. GRAPHICAL ABSTRACT: UF0001